Derivation of Sendai-Virus-Reprogrammed Human iPSCs-Neuronal Precursors: In Vitro and In Vivo Post-grafting Safety Characterization - Shigyo, Michiko; Kobayashi, Yoshiomi; Platoshyn, Oleksandr; Marsala, Silvia; Kato Jr, Tomohisa; Takamura, Naoki; Yoshida, Kenji; Kishino, Akiyoshi; Bravo-Hernandez, Mariana; Juhas, Stefan; Juhasova, Jana; Studenovska, Hana; et al. (Cell transplantation, 2023)
The critical requirements in developing clinical-grade human-induced pluripotent stem cells–derived neural precursors (hiPSCs-NPCs) are defined by expandability, genetic stability, predictable in vivo post-grafting differentiation, and acceptable safety profile. Here, we report on the use of manual-selection protocol for generating expandable and stable human NPCs from induced pluripotent stem cells. The hiPSCs were generated by the reprogramming of peripheral blood mononuclear cells with Sendai-virus (SeV) vector encoding Yamanaka factors. After induction of neural rosettes, morphologically defined NPC colonies were manually harvested, re-plated, and expanded for up to 20 passages. Established NPCs showed normal karyotype, expression of typical NPCs markers at the proliferative stage, and ability to generate functional, calcium oscillating GABAergic or glutamatergic neurons after in vitro differentiation. Grafted NPCs into the striatum or spinal cord of immunodeficient rats showed progressive maturation and expression of early and late human-specific neuronal and glial markers at 2 or 6 months post-grafting. No tumor formation was seen in NPCs-grafted brain or spinal cord samples. These data demonstrate the effective use of in vitro manual-selection protocol to generate safe and expandable NPCs from hiPSCs cells. This protocol has the potential to be used to generate GMP (Good Manufacturing Practice)-grade NPCs from hiPSCs for future clinical use.